Health economics of obesity: new insights - Wolf, Anne (Henry Stewart Talks, 2007)
International cost estimates, Benchmark cost estimates, Direct cost in the US by demographics, Impact on productivity, Impact of weight loss on health care costs: lifestyle, pharmacotherapy and surgical interventions
Archived at 2021/02/25